Digitalisasi Promosi Pendidikan Islam sebagai Inovasi Strategis di Lembaga Pesantren: Studi Kasus Pondok Pesantren Nurus Syam Bondowoso - Muhammad Nauval Izzul Kamal (Yayasan Literasi Altruis Khatulistiwa, 2025)
Digital transformation has penetrated various sectors of life, including Islamic education. Traditional Islamic boarding schools (pesantren) now face both challenges and opportunities to adopt digital strategies in promoting their educational identity and excellence. This study aims to examine how digital promotion is implemented at Pondok Pesantren Nurus Syam Bondowoso as a strategic innovation in responding to contemporary needs. A descriptive qualitative approach was employed using a case study method. Data were collected through observations, in-depth interviews with pesantren administrators, and documentation of digital media used by the institution. The findings indicate that the pesantren utilizes various digital platforms such as social media, official websites, and digital da'wah content to build a progressive and inclusive institutional image. This strategy not only expands promotional reach but also shapes the digital identity of the pesantren to align with younger generations. Digital promotion has proven effective in increasing public engagement, attracting new students, and strengthening the network of Islamic educational da'wah. These findings highlight the importance of human resource readiness and digital infrastructure in sustaining technology-based promotional innovations within pesantren environments.